Long-Term Efficacy of Pembrolizumab and the Clinical Utility of ctDNA in Locally Advanced dMMR/MSI-H Solid Tumors - Michael LaPelusa; Wei Qiao; Bryan Iorgulescu; Francis San Lucas; Keyur Patel; Deepak Bhamidipati; Jane Varkey Thomas; Nancy You; Wai Chin Foo; Dipen Maru; Selvi Thirumurthi; Van Morris; et al. (Nature Communications)
Abstract Neoadjuvant immunotherapy can induce pathologic complete response (pCR) in patients with localized deficient mismatch repair (dMMR)/microsatellite instability-high (MSI-H) tumors. The long-term outcomes of these patients are unknown, as is the clinical utility of measuring circulating tumor DNA (ctDNA). Follow-up was evaluated in patients enrolled in a phase II trial (NCT04082572) that evaluated the efficacy and safety of pembrolizumab in patients with localized dMMR/MSI-H tumors. The primary outcomes of this trial have previously been reported. 3-year EFS and OS rates were 80% (95% CI: 66% – 93%) and 94% (95% CI: 86% – 100%). Patients without detectable ctDNA after pembrolizumab had higher 3-year EFS and OS rates than patients with detectable ctDNA after pembrolizumab (3-year EFS 92% vs 20%; p < 0.001, 3-year OS 100% vs 80%; p < 0.001). Patients with colorectal cancer (CRC) who had undetectable ctDNA after pembrolizumab were more likely to have pCR compared to those with detectable ctDNA after pembrolizumab (91% vs 0%; p = 0.03). Patients with CRC who were managed non-operatively and had undetectable ctDNA after pembrolizumab had a higher 2-year EFS rate than patients with detectable ctDNA after pembrolizumab (100% vs 33%; p = 0.03). Pembrolizumab demonstrates long-term efficacy in patients with localized dMMR/MSI-H tumors.